Nonlinear Seepage Model of Gas Transport in Multiscale Shale Gas Reservoirs and Productivity Analysis of Fractured Well - Ting Huang; Xiao Guo; Kun Wang (Journal of Chemistry)
Shale is abundant in nanoscale pores, so gas flow in shales cannot be simply represented by Darcy formula anymore. It is crucial to figure out the influence of gas flow in nano/micro pores on actual productivity, which can provide basic theories for optimizing parameters and improving the gas production from engineering perspective. This paper considers the effects of slippage and diffusion in nanoscale based on Beskok-Karniadakis (BK) equation, which can be applicable for different flow regimes including continuum flow, slip flow, transition flow, and free-molecule flow. A new non-Darcy equation was developed based on the analysis of effects of high order terms of BK equation on permeability correction factor. By using the conformal transformation principle and pressure coupling method, we established the productivity formula of fractured well (infinite and limited conductivity) satisfying mass variable seepage flowing in fractures. The simulation results have been compared with field data and influencing parameters are analyzed thoroughly. It is concluded that slippage effect affects gas production of fractured well when wellbore pressure is less than 15 MPa, and the effects of slippage and diffusion have greater influence on gas production of fractured well for reservoir with smaller permeability, especially when permeability is at nano-Darcy scale.